TRANSFORMASI MEDIA BISNIS DI ERA PANDEMI COVID-19 - Khoerunisa, Syfa (JIKE : Jurnal Ilmu Komunikasi Efek, 2022)
This study aims to analyze the transformation of business owners from conventional methods to digital platforms to maintain their business in the era of the covid-19 pandemic. Several policies have been implemented by the government to suppress the spread of COVID-19, one of which is large-scale social restrictions. This policy has a serious impact on business people in Indonesia. These business people change the style of doing business and communicating with customers, one of which is in marketing and offering types of products to the wider community. Most of the business actors at this time choose to use social media and online store applications that are more accessible to all circles of society. Several social networks and online store applications that are widely used by business actors include Facebook, Instagram, TikTok, Shopee, Zalora, Tokopedia, Lazada, and so on. Keywords:communication, media,  pandemic, transformation